Highly efficient second harmonic generation of thin film lithium niobate nanograting near bound states in the continuum. (21st May 2021) - Huang, Zhijin; Wang, Mengjia; Li, Yang; Shang, Jumei; Li, Ke; Qiu, Wentao; Dong, Jiangli; Guan, Heyuan; Chen, Zhe; Lu, Huihui
Abstract: Bound states in the continuum (BICs) are ubiquitous physical phenomena where such states occur due to strong coupling between leaky modes in side lossy systems. BICs in meta-optics and nanophotonics enable optical mode confinement to strengthen local field enhancement in nonlinear optics. In this study, we numerically investigate second-harmonic generation (SHG) in the vicinity of BICs with a photonic structure comprising one-dimensional nanogratings and a slab waveguide made of lithium niobate (LiNbO3, LN). By breaking the symmetry of LN nanogratings, BICs transition to quasi-BICs, which enable strong local field confinement inside LN slab waveguide to be supported, thereby resulting in improving SHG conversion with lower pump power of fundamental frequency (FW). With a peak intensity of 1.33 GW cm −2 at the FW, our structure features a second-harmonic conversion efficiency up to 8.13 × 10 −5 at quasi-BICs. We believe that our results will facilitate the application of LN in integrated nonlinear nanophotonic.